EDUKASI PENCEGAHAN GAGAL GINJAL PADA MASYARAKAT DI DESA SEI LIMBAT KECAMATAN SELESAI KABUPATEN LANGKAT TAHUN 2025 - Herawati, Leli; Wahyuni, Sri; Ananda, Ichfad; Hasibuan, Nur Suci; Sarwah, Jamila (INSTITUT KESEHATAN DELI HUSADA, 2025)
This Community Service (PkM) activity, titled “Education on the Prevention of Chronic Kidney Failure among the Community in Sei Limbat Village, Selesai Subdistrict, Langkat Regency, 2025,” was conducted to address the low awareness and interest of the community in preventing kidney failure, as reflected in their limited use of healthcare services and reluctance to undergo regular check-ups. A preliminary study showed that most respondents (6 out of 10) lacked knowledge about home-based prevention of kidney failure. To overcome this issue, the program provided free early detection of kidney disease, especially for the elderly, along with educational and counseling sessions delivered individually and in groups. Held on June 11, 2025, in Sei Limbat Village and attended by 26 participants, the activity generated strong enthusiasm, with participants actively engaging in discussions and demonstrating improved understanding of preventive measures. These outcomes indicate that the program effectively enhanced community knowledge and awareness regarding chronic kidney failure prevention.